The relationship between plasma serotonin and kynurenine pathway metabolite levels and the treatment response to escitalopram and desvenlafaxine - Sun, Yu; Drevets, Wayne; Turecki, Gustavo; Li, Qingqin S. (Brain, behavior, and immunity, 2020)
•Response to escitalopram was associated with higher baseline serotonin levels.•Response to escitalopram was associated with lower baseline Kyn/Trp ratio and quinolinic acid (QuinA)/tryptophan (Trp) ratio.•Remitters to escitalopram showed significant increases in KynA/3HK ratio. The response of patients with major depressive disorders (MDD) to antidepressant treatments have been shown to be affected by multiple factors, including disease severity and inflammation. Increasing evidence indicates that the kynurenine metabolic pathway is activated by inflammation in MDD patients and plays a role in the pathophysiology of depression. Antidepressant treatments have been reported to affect kynurenine pathway metabolite levels as well. This study investigates differential associations between the antidepressant treatment outcome to escitalopram versus desvenlafaxine with the pre-treatment and post-treatment-changes in serotonin and kynurenine pathway metabolite levels. The levels of serotonin and of kynurenine pathway metabolites were measured in plasma using liquid chromatography-mass spectrometry (LC-MS) in 161 currently depressed patients with MDD at baseline and after 8 weeks of treatment with either escitalopram or desvenlafaxine. Treatment response was defined conventionally by a reduction of at least 50% in the Hamilton Depression Rating Scale 21 item (HAMD-21) total score from baseline; remission was defined by reaching a post-treatment HAMD-21 score ≤7. Response to escitalopram treatment was associated with higher baseline serotonin levels (p = 0.022), lower baseline kynurenine (Kyn)/tryptophan (Trp) ratio (p = 0.008) and lower baseline quinolinic acid (QuinA)/tryptophan (Trp) ratio (p = 0.047), suggesting a lower inflammation state. Greater improvement in depression symptoms as measured by percent change of HAMD-21 score from baseline was also associated with higher baseline serotonin levels (p = 0.033) in escitalopram treatment arm. Furthermore, remitters to escitalopram treatment showed significant increases in the kynurenic acid (KynA)/3-hydroxykynurenine (3HK) ratio after treatment (p = 0.015). In contrast, response to desvenlafaxine treatment was not associated with any metabolite analyzed. We also confirmed a previous report that plasma serotonin levels are lower in MDD patients compared to healthy controls (p = 0.004) and that the kynurenine plasma level is negatively associated with depression symptom severity (p = 0.047). In MDD patients the antidepressant response to escitalopram was positively associated with baseline serotonin levels and inversely associated with activation of the kynurenine pathway. These results appear consistent with previous literature showing that biomarker evidence of inflammation is associated with lower response to antidepressants from the selective serotonin reuptake inhibitor class. Moreover, increases in the kynurenic acid (KynA)/3-hydroxykynurenine (3HK) ratio, which previously has been characterized as a neuroprotective index, were associated with full remission under escitalopram treatment.